OCHRONA CZŁONKÓW RODZINY SPADKODAWCY NA TLE HISTORYCZNOPRAWNYM ORAZ PRAWNOPORÓWNAWCZYM - Borysiak, Witold (Zeszyty Prawnicze, 2017)
Protection of the Deceased’s Family Members in the Historical and Comparative Perspective Summary All of the contemporary legal systems provide special regulations which protect the deceased’s family members from order’s occurring in his will. Freedom of the testacy is one of the most important rules in the law of successions. Nevertheless it should have limits – the most common example of that situation exists when deceased’s orders omits entirely the members of his closest family. The origins of that protection could be found in the Roman Law. This legal system creates two types of protection – “counter-will formal succession” (previous in the Roman Law evolution) and “counter-will material succession”. According to the first one, testator has a duty to disinherit all of his sons (sui heredes) in the clear and precise words (exhereditatio nominatim). He should also disinherit all of the other members of his family (such as daughters or grandchildren); however he has possibility to do so in a general clause. His will would be overthrown if he has not disinherited members of his family. In that case entitled persons acquired the status of the heirs. This system gave no property rights to descendants of the deceased - they had only right to be an heir or to be disinherit (which was described in the rule that sui heredes should be set up as heirs or should be disinherit - sui heredes aut instituendi sunt aut exheredandi). According to the second type of protection if deceased did not gave part of his property (so called pars legitima) to the entitled persons they have a legal claim (querela inofficiosi testamenti) to declare his will void. On the ground of that regulation existed fiction that testator, who disinherit the members of his closed family, acting in the mental disorder (cum colore insaniae) and violates his father duties (action contra officium pietatis). Roman Law protects the entitled person also against all of the donationes (those performing during the live of testator and mortis causa donations) in which deceased try to evade statutory protection of his family members.